BAGAIMANAKAH TINGKAT KESEHATAN BANK BUMN DI INDONESIA SETELAH KRISIS KEUANGAN 2008 : CAMELS ANALYSIS - Dhistianti Mei Rachmawantari; Ayu Puspitaningtyas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The CAMELS method in this study is used to analyze and evaluate the financial performance of state-owned banks in Indonesia and is regulated in Bank Indonesia Regulation Number 6/10 / PBI / 2004 concerning the Rating System for Commercial Banks and Bank Indonesia Regulation Number 9/1 / PBI / 2007 concerning Rating System Health of Commercial Banks Based on Sharia Principles. Based on the results of the study, it can be concluded that from the four state-owned banks studied are Bank Mandiri, BRI, BNI and BTN, after 2008 financial crisis (2009-2016), the best bank health owned by Bank Rakyat Indonesia (BRI), it is shown by the value of CAMELS ratio on all indicators used always are in a position to follow the limits set by Bank Indonesia. While the weakest bank soundness is shown by the State Savings Bank (BTN) with the value of NPM ratio under the terms and LDR above the provisions of Bank Indonesia for healthy predicate and it also has the highest level of risk among the other three banks.